KOMPETENSI ARSIPARIS DALAM PENGELOLAAN ARSIP DI UIN MAULANA MALIK IBRAHIM MALANG - Moh. Sholahuddin; Nurul Imamah Aini (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2022)
State Islamic University of Maulana Malik Ibrahim Malang is a university with the status of a Public Service Agency and is required to improve the quality of its public services, including the quality of services and archive management. This study aims to determine the effect of archivist competence on archive management at State Islamic University of Maulana Malik Ibrahim Malang, so it is hoped that the results can be used as a basis for consideration of policy making in managing archives to be better. This study uses a descriptive verification approach that describes the facts and data as they are. The object of this research is the competence of archivists and archive managers and their influence on archive management, with the population being archivists and archive managers at State Islamic University of Maulana Malik Ibrahim Malang. The results of this study indicate that the influence of archivist competence is not very significant in archive management at State Islamic University of Maulana Malik Ibrahim Malang because the influence of knowledge on the performance of the p-value (0.171) > (0.05) has no significant effect, the influence of skills on the performance of the p-value (0.305) > (0.05) had no significant effect, and the effect of attitude on the performance of the p-value (0.069) > (0.05) had no significant effect.